Analysis Lattice Constant of Ceramic SrTiO3 Doped Cuprum(II) Acetate Cube Structure by Cramer-Cohen Method - Handayani, Pipit; Mufarrohah, Fatihatul; Asih, Asih; Rahmawaty, Vania; Santi, Maya Ary; Rukyati, Anis Munir; Siskandar, Ridwan; Syafutra, Heriyanto; Pratama, Erdiansyah; Setiawan, Ardian Arif; Irzaman, Irzaman (STKIP Singkawang, 2024)
Analysis of SrTiO3 ceramics with the doping Cuprum(II) acetate (Cu(CH3COO)2), the variation in the concentration of doping used 0%; 0,5%; and 1% using the solid state reaction method was successful. The annealing process is carried out starting from room temperature then raised to an annealing temperature of 850 oC with a temperature increase of 1,67 oC / minute and held constant for 8 hours. Next proceed with the cooling process until it returns to room temperature for 13 hours. Analysis of XRD data using the Cramer-Cohen method yielded a lattice parameter of 3,909 Å; 3,906 Å; and 3,905 Å, a cubic crystal structure.